Cultivating Moral Character In The Teaching Of Pancasila And Citizenship Education In Elementary Schools - Khotimah, Putri; Sutama, S; Adnan, Mazlini (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of the research in this article is 1) to describe the moral character in the customs of Pancasila and citizenship education learning. 2) to describe the moral character in information media in Pancasila and citizenshipeduca-tion learning. Methodology: This type of research is descriptive qualitative, with the subjects being the homeroom teachers and 4th-grade students of SDIT Muhammadiyah Al-Kautsar. Data collection through in-depth interviews, participatory observa-tion, and document analysis with method triangulation. The data analysis of this research includes data reduction, data presentation, and conclusion draw-ing. Results: 1) This study shows that the character of morality in the cultural habituation of this research in the cultivation of moral character at SDIT Muhammadiyah Al-Kautsar has been carried out well. The school has carried out various routine activities, such as group Quran recitation, congregational prayers, and com-munal meals. 2) This research shows that the information media used by teachers involves discussing with parents to monitor daily activities in the home environment, ensuring that children are well-supervised. Applications/Originality/Value: In previous research, there has been no discussion on the cultivation of moral character with indicators such as customs and information media. Therefore, this research is important to explore the indicators used in the cultivation of moral character. The cultivation of moral character through customs and in-formation media is expected to be applied by students during their activities in the school, home, and community environments.